The microcycle of inflammation and performance changes after a basketball match - Chatzinikolaou, A.; Draganidis, D.; Avloniti, A.; Karipidis, A.; Jamurtas, A. Z.; Skevaki, C. L.; Tsoukas, D.; Sovatzidis, A.; Theodorou, A.; Kambas, A.; Papassotiriou, I.; Taxildaris, K.; et al. (Journal of Sports Sciences, 2014)
Basketball incorporates intense eccentric muscle activity that induces muscle microtrauma and an inflammatory response. This study investigated time-dependent inflammatory and performance responses during a weekly microcycle after a basketball match. Twenty elite-standard players underwent a trial that comprised a match followed by a 6-day simulated in-season microcycle. The trial was preceded by a control condition that did not have a match. Blood sampling and tests of maximal-intensity exercise performance and muscle damage occurred before each condition, immediately after the match and daily thereafter for 6 consecutive days. The match induced marked increases in heart rate, lactate, ammonia, glucose, non-esterified fatty acids and triglycerides. Performance deteriorated for 24-48 h after the match, whereas knee flexor and extensor soreness increased for 48 and 24 h post-match, respectively. Inflammatory (leukocytes, C-reactive protein, creatine kinase activity, adhesion molecules, cortisol, uric acid and cytokines) and oxidative stress (malondialdehyde, protein carbonyls, oxidised glutathione, antioxidant capacity, catalase and glutathione peroxidase) markers increased for ~24 h and subsided thereafter. Reduced glutathione declined for 24 h after exercise. These results suggest that a basketball match elicits moderate and relatively brief (~24-48 h) inflammatory responses, is associated with marked but short-lived performance deterioration, but is less stressful than other intermittent-type sports.